Kedudukan Akal dalam Pendalilan Akidah (Sains Humanika, 2013)
The logical reasoning is one of the most important sources in Islamic theology tradition, besides the main source Quran and Hadith. The position of logical reasoning is recognized by the Sunni’s scholar because it is able to produce the level of confidence to believe in God. However, a number of schools of theology like Hashawiyyah refute the logical reasoning and claimed Sunni, especially Asharite and Maturidi theologians were influenced by Mutazilite methodology, which prioritizes the logical reasoning than divine revelation. The implications of this accusation make several Muslims denied the logical reasoning in theology tradition, even followers Asharite and Maturidi also equated with Mutazilite. This study employs qualitative methods with a special focus on document analysis method in analyzing and examines the Sunni theology framework to prove that Sunni owned their methodology in interacting with the logical reasoning. Even this article also highlighted Hashawiyyah and Mutazilite stance toward the issue and become a polemic between them. The study found that the approach of the Sunni in acceptance the logical reasoning based on accurate proof and argument to differentiate them from Mutazilite and Hashawiyyah. This is in line with the Qur'an and the Hadith, which also recognizes the advantages of the human reason. Additionally, this study concluded that the human reason also has limitations in knowing the reality of God and Islamic laws.
Keywords: Logical reasoning; divine revelation; theology; Sunni